A Review on Recent Advances on Magnesia-Doloma Refractories by Nano-Technology. - Salman Ghasemi-Kahrizsangi; Ebrahim Karamian; Hassan Gheisari Dehsheikh; Ahmad Ghasemi-Kahrizsangi (Journal of Water and Environmental Nanotechnology, 2017)
Due to exhibiting an excellent chemical resistance against basic environments at high temperature, good thermal shock resistance, thermodynamic stability in the presence of carbon, and a suitable abrasion resistance, MgO-CaO refractories are widely used in argon-oxygen decarburization furnaces in the metallurgy industry and cement rotary kilns. Furthermore, MgO-CaO refractories are beneficial to removing inclusions from molten steels; thus, they have been considered to be one of the effective refractory types for processing clean steel products. Also, MgO-CaO materials have become one of the attractive steelmaking refractories because of their low cost and high ore reserves.  However, in spite of these primary advantages, the application of MgO-CaO refractories has not been popular due to its tendency to hydration when exposed to the atmosphere.  In world most of MgO-CaO bricks producers used of organic components such as tar, pitch, and peck for produce MgO-CaO refractories. But during the application of these bricks in steel and cement and industrials, they released CO and CO2 gases to air and pollute the atmosphere. For this reason, recently some researcher investigate the effect of additive nanoparticles on MgO-CaO refractories performance. They reported the used of Nano-additive have acceptable results and additive nanoparticles can replace by aforementioned environment contaminating organic compounds. In this study, we reviewed all effort that done for improving the hydration resistance of MgO-CaO refractories by application of Nano-additives with an emphasis on the beneficial the use of additives nanoparticle for reduction of environmental pollution by various industries which used of MgO-CaO refractory bricks.